DEVELOPMENT OF AKM-BASED QUESTIONS TO FACILITATE STUDENTS' NUMERACY SKILLS - Irwandi, Bayu; Hutapea, Nahor Murani; Yuanita, Putri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study was motivated by the importance of numeracy as a core competency required to face 21st-century challenges. However, results of the Minimum Competency Assessment (AKM) reveal that more than half of vocational high school (SMK) students in Indonesia fall below the minimum proficiency level in numeracy. This condition occurs due to the limited availability of practice items for students and the limited ability of teachers to develop AKM-based questions. The aim of this study was to develop valid and reliable AKM-oriented numeracy items to support students’ numeracy improvement. The development model employed was development studies, consisting of two stages: the preliminary stage (analysis and design) and the formative evaluation stage. The research was conducted at SMK Abdurrab Pekanbaru using test and interview methods for data collection. During the formative evaluation stage, the developed items were tested on 32 students to assess validity, reliability, difficulty level, and discriminating power. The results showed that 18 test items were valid, comprising 2 multiple-choice, 4 true/false, 3 matching, and 9 essay items. Reliability testing using the KR-20 formula for objective items produced a coefficient of 0.847 (very high), while Cronbach’s Alpha for essay items was 0.873 (very high). Difficulty analysis indicated 3 easy, 14 moderate, and 1 difficult item. Discrimination analysis showed that 15 items had good discriminating power and 3 had moderate levels. In conclusion, the 18 developed items were considered suitable for measuring and improving students’ numeracy skills and can serve as a reference for teachers in designing AKM-based assessments.